Strategies to Transform Dream into Reality: How can India Participate for Better Performance in Mathematics at Timss? - Parekh, Himanshu Sureshchandra (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Trends in International Mathematics and Science Study (TIMSS) is established by International Associations for the Evaluation of Educational Achievement (IEA), U.S.A and aimed at allowing educational systems worldwide to compare students' educational achievement as well as to learn from the experiences of others in designing effective education policy. TIMSS has been held every four years since 1995 and it includes a test for grades 4 and 8 in Mathematics and Science subjects. India, dreaming of becoming a developed nation in the world, has an attitude of not participating at international assessment programmes. Such attitude is not only depriving Indian Education System of international quality but is also obstructing the transformation process of India from a developing to a developed nation.  This study is an investigation of three research questions: What is the system of TIMSS in the subject of Mathematics? What is the present status of Mathematics Education in India with reference to the system of TIMSS? What strategies should India adopt to participate for better performance in Mathematics at TIMSS? The study revealed that overall scenario of Mathematics Education in India, with reference to the system of TIMSS, is very poor. The study identified certain major barriers, such as, lack of linkage of the international assessment norms with the Mathematics textbooks, inability of the system to identify and to develop the Mathematical skills of the gifted children, lacking of policy international norms as well as parameters in terms of achieving global competitiveness, corruption, non-uniform policy in Mathematics Education across the country, non professional attitude of teachers, sub-standard provisions for the professional development of Mathematics teachers, inefficiency of the monitoring and assessing system etc. in achieving the dream of better performance of India at TIMSS. The study suggested appropriate strategies in overcoming these barriers.